A DFT study of the role of the Lewis acid catalysts in the [3 + 2] cycloaddition reaction of the electrophilic nitrone isomer of methyl glyoxylate oxime with nucleophilic cyclopentene1. Issue 79 (28th August 2015) - Nacereddine, Abdelmalek Khorief; Layeb, Hatem; Chafaa, Fouad; Yahia, Wassila; Djerourou, Abdelhafid; Domingo, Luis Ramon
<x xml:space="preserve">Abstract</x> The mechanism and stereoselectivity of the BH3-catalysed 32CA reaction between C-methoxycarbonyl nitrone and cyclopentene has been studied using MPWB1K/6-31G(d) computational level.